The Future Is Open and Shapable: Using Solar Speculative Fiction to Foster Learner Agency. (November 2021) - Jordan, Michelle; Bernier, Jeremy; Zuiker, Steven
Speculative fiction is a powerful medium to explore possible futures, inviting literacy researchers and educators to consider the value of futures thinking as a tool for eliciting learners' hopeful narratives about equitable, sustainable futures for their communities. Yet, when asked to imagine the future, adults and youth alike often envision dystopian stories and fail to consider the interdependencies between technological innovations and the social, economic, and environmental contexts they shape. Moreover, current pedagogic strategies for thinking about the future encourage globalized perspectives rather than stories localized in learners' lived contexts. Using design-based research methods and informed by ecological theories that assume learners exercise agency through their actions that bring together past, present, and future, our team developed conjectures about how futures thinking might support learners' agency in relation to sustainability activism and environmental justice. Data analyzed to test our conjectures were 18 solar futures narratives written by adult and youth participants in a solar energy research program. Findings show promise for writing practices that foster sustainability and climate change learning.